The Content of the Principle of Bona Fides in Family Law - Ya. A. Glebovsky (Ученые записки Казанского университета: Серия Гуманитарные науки, 2024)
This article unveils the content and scope of the principle of bona fides in the Russian family law. The implied duty of good faith in the property and non-property aspects of family relations was analyzed. This is important because legal scholars have traditionally attributed it to one of the basic principles of civil law and thus understudied its role within family law. Here, it was defined how the principle of bona fides applies specifically to family law, particularly to what regards property and non-property implications.The use of the principle of bona fides in court hearings on family disputes was discussed. Its impact on the content of the concept of good faith was considered. The differences between the interpretations of good faith in civil and family laws were highlighted. The theoretical conclusions were supported by the examples from real court cases.